Conceptualizing trust-based online behavior model for Muslim consumers - Suhaimi, Mohd Adam; Mohamed Razi, Mohamed Jalaldeen; Hussin, Husnayati; Muhammad, Muhd Rosydi; Muhammad, Marjan; Abdullah, Kalthom (2013)

(untitled)
Muslim consumers are beginning to be more concerned whether the current e-commerce processes are mixed with un-Islamic elements such as, riba (interest), gharar (uncertainty), and Maisir (gambling). To clarify the misconception, it is suggested that an assurance be given by a reputable Islamic religious authority to the effect that Internet seller complies with an Islamic law (Shariah) -compliant e-commerce model. However, Muslim consumers’ perception in this regard is yet to be measured. To fill this gap, the present work presents a comprehensive testable research framework that can be used to investigate the Muslim consumers’ perceived behavior in e-commerce environment. In addition to third party assurance from an Islamic religious authority, the other factors such as trustworthiness of Internet sellers, perceived risk of online transaction and quality of the websites also have been included in the framework.